Reaksi Pasar terhadap Pengumuman Bond Rating : Studi Empiris di Bursa Efek Indonesia - B11111124, Fitriana (Jurnal Manajemen Update, 2015)
The results of this study found that there was no difference between stock returns and trading volume activity (TVA) companies entering grade A, B and C in the time before, during and after the announcement of the bond rating happened. Looked at the results of paired samples t-test and independent t-test that the probability value greater than 0.05 and T value was smaller than t table so H0 was accepted. This means that the market reacts to changes in the ordinary course rating of the bonds and not excessive speculation. Looked that normal return always appear around the announcement date and shows that the announcement of bond rating does not contain meaningful information for investors. Keywords: bond rating, average abnormal return, trading volume activity, events study